2003
DOI: 10.1086/376580
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Selection Causes a Coevolutionary Arms Race between Crossbills and Lodgepole Pine

Abstract: Few studies have shown both reciprocal selection and reciprocal adaptations for a coevolving system in the wild. The goal of our study was to determine whether the patterns of selection on Rocky Mountain lodgepole pine (Pinus contorta spp. latifolia) and red crossbills (Loxia curvirostra complex) were concordant with earlier published evidence of reciprocal adaptations in lodgepole pine and crossbills on isolated mountain ranges in the absence of red squirrels (Tamiasciurus hudsonicus). We found that selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
348
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(387 citation statements)
references
References 56 publications
29
348
1
1
Order By: Relevance
“…Exceptions to this statement lie in the character displacement literature, in which researchers have shown that species exhibit reciprocal shifts in trait values in response to the presence or absence of other species (Schluter et al ., 1985;Benkman, 2003;Knouft, 2003). The community context of diffuse coevolution is probably being most closely addressed in a set of studies by Benkman and colleagues on crossbills, red squirrels, insects, and lodgepole pines (Benkman, 1996(Benkman, , 1999Benkman et al ., 2001Benkman et al ., , 2003. Pine cone morphology changes in response to directional selection from all cone predators -moths, red squirrels, and crossbills, and each herbivore in isolation results in a different pattern of selection on cone morphology (pair-wise selection).…”
Section: Diffuse Coevolution Diffuse Selection and Diffuse Evolutionmentioning
confidence: 99%
“…Exceptions to this statement lie in the character displacement literature, in which researchers have shown that species exhibit reciprocal shifts in trait values in response to the presence or absence of other species (Schluter et al ., 1985;Benkman, 2003;Knouft, 2003). The community context of diffuse coevolution is probably being most closely addressed in a set of studies by Benkman and colleagues on crossbills, red squirrels, insects, and lodgepole pines (Benkman, 1996(Benkman, , 1999Benkman et al ., 2001Benkman et al ., , 2003. Pine cone morphology changes in response to directional selection from all cone predators -moths, red squirrels, and crossbills, and each herbivore in isolation results in a different pattern of selection on cone morphology (pair-wise selection).…”
Section: Diffuse Coevolution Diffuse Selection and Diffuse Evolutionmentioning
confidence: 99%
“…Consequently, understanding local hierarchical interactions across a species' geographic range is crucial for understanding coevolution (Thompson 1994(Thompson , 1997. Although interspecific interactions rarely involve only two species, community context has only recently been included in theoretical models and empirical studies to evaluate coevolutionary trajectories in parasite systems and other model systems of competition (e.g., Benkman 1999, Benkman et al 2003, Brandt and Foitzik 2004, Gandon 2004. A primary focus has been the effect of multiple-target use on the outcomes of coevolutionary interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Increased cone size exerts reciprocal selection on crossbills for increased beak size. However, in areas where red squirrels (Tamiasciurus hudsonicus) are the dominant seed predator and out-compete crossbills, the birds adapt to average cone size and have smaller beaks (7,8). Because populations of crossbills with different beak sizes tend not to interbreed, crossbills in regions with and without squirrels have undergone speciation (9).…”
mentioning
confidence: 99%